2015
DOI: 10.1080/02635143.2014.971733
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a popular science promotion program on nanotechnology for elementary school students in I-Lan City

Abstract: Background: Nanotechnology education has become an urgent priority to nurture skilled human resources for the rapidly developing nanotechnology-related industries. The promotion of popular science education focusing on nanotechnology is an ideal approach to bridge the gaps in formal curricula, and to stimulate curiosity about and interest in nanotechnology among schoolchildren. Purpose: The objective of this study was to evaluate the effectiveness of the Nanotechnology-based Popular Science Education Promotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 18 publications
0
15
0
2
Order By: Relevance
“…In fact, connecting NST with the workforce needs became compulsory education. Notably, NST educators argued that since primary school students constitute the future workforce in NST, their early contact with the emerging field is essential [18]. However, we consider that the teaching of NST in primary school education is not strictly oriented towards directing the students to pursue a relevant professional career.…”
Section: Educational Significance Of Nst: a Review Of The Literaturementioning
confidence: 96%
See 1 more Smart Citation
“…In fact, connecting NST with the workforce needs became compulsory education. Notably, NST educators argued that since primary school students constitute the future workforce in NST, their early contact with the emerging field is essential [18]. However, we consider that the teaching of NST in primary school education is not strictly oriented towards directing the students to pursue a relevant professional career.…”
Section: Educational Significance Of Nst: a Review Of The Literaturementioning
confidence: 96%
“…Instead, it is closely linked to one of the goals of science education, which is to familiarize students with new research and technology opportunities and help them enhance their ambitions. This is a perspective that students seem to find really fascinating about science [18,19].…”
Section: Educational Significance Of Nst: a Review Of The Literaturementioning
confidence: 99%
“…Similarly, in another study by Lin (2015) ISSN 2157-6076 2020 in the natural world'; 'Nanomaterials and their scaling effects'; and 'Definition, characteristics, and applications of nanotechnology.' The result indicated positive change related to nanotechnology concepts for more than 30% of students.…”
Section: C-1) In Secondary Educationmentioning
confidence: 99%
“…Nugent et al (2010) and Anand and Dogan (2021) note that the purpose of learning activities in informal curricula is to provide students with opportunities to engage more deeply in learning activities. Lin et al (2015) arranged popular science activities through the Nanotechnologybased Popular Science Education Promotion and Teaching (NPSEPT) program. The results showed that the participants, elementary school students, achieved significant gains in nanotechnology learning performance and outcomes.…”
Section: Effectiveness Of Popular Science Activities In Informal Curr...mentioning
confidence: 99%